Revision of 'A Catalogue of the known Species of the World belonging to the Subfamily Aphidiinae' (Hymenoptera: Braconidae). - Narayanan, E. S.; Subba Rao, B. R.; Sharma, A. K.; Starý, Petr (Contributions to Entomology = Beiträge zur Entomologie, 1962)
The authors present a revision of their preceding catalogue incorporating scientific work on this subject done since 1957, except the genus Aphidius Nees, according to the need of a thorough reexamination of some Aphidius dealt with in the authors' earlier paper.Nomenclatural Actscaudacanthus (Smith, 1944) (Acanthocaudus), comb. n. hitherto Trioxys (Acanthocaudus) caudacanthus Smith, 1944schlingeri (Muesebeck, 1958) (Acanthocaudus), comb. n. hitherto Trioxys (Acanthocaudus) schlingeri Muesebeck, 1958tissoti (Smith, 1944) (Acanthocaudus), comb. n. hitherto Trioxys (Acanthocaudus) tissoti Smith, 1944